Impact of stacking order on the microstructural properties of Cu2ZnGeSe4 thin film absorber layer. (May 2018) - Mary, G. Swapna; Chandra, G. Hema; Sunil, M. Anantha; Subbaiah, Y.P. Venkata; Gupta, Mukul; Rao, R. Prasada
Abstract: Six possible multiple stacks of Cu-ZnSe-Ge with selenium incorporation at a precursor stage were prepared using electron beam evaporation followed by vacuum selenization at 475 °C for 30 min to investigate the role of stacking order on the growth and properties of Cu2 ZnGeSe4 films. The X-ray diffraction measurements affirm the existence of various binary and ternary phases (ZnSe, Cu2 Se, GeSe2 and Cu2 GeSe3 ) for all the precursor stacks. These phases are completely diminished after selenization at 475 °C except a minor co-existence of ZnSe (111) phase along with dominant Cu2 ZnGeSe4 (112) phase for stack A: (Cu/Se/ZnSe/Se/Ge/Se) × 4. The Raman measurements for selenized multiple stack A, revealed two major A 3, A 1 modes at 206 cm −1 and 176 cm −1 and one minor E 5 mode at 270 cm −1 corresponding to CZGSe phase. The surface morphology and the elemental distribution across the thickness found to vary significantly with the change of stacking order. The selenized multiple stacks A films shows densely packed flake and capsule shaped grains. The selenized stack A found to have a direct energy band gap of 1.60 eV, showing p -type conductivity with a Hall mobility of 22 cm 2 (Vs) −1 . Highlights: CZGSe thin films are prepared by selenization of multiple stacks using of Cu-ZnSe-Ge at 475 °C for 30 min. Effect of stacking order on the composition, micro-structure, opto-electronic properties of CZGSe thin films was studied. Based in the SIMS, XRD, Raman and optical measurements the location of secondary phases was illustrated. The selenized multiple stacks A films shows densely packed flake and capsule shaped grains.